Analysis of the Carrying Capacity and the Total Maximum Daily Loads of the Karang Mumus Sub-watershed in Samarinda City Using the WASP Method - Achmad Diansyukma; Sri Puji Saraswati; Ahmad Tawfiequrrahman Yuliansyah (Journal of the Civil Engineering Forum, 2021)
Watershed is a multi-aspect ecological system, which functions as a source of water resources, in order to meet daily needs. It also motivates both economical and life matters, as well as serve as a sanitary channel for the surrounding community. Watershed also generates pollutants, which are known to potentially cause a decrease in river water quality. The degradation of river habitats that are caused by high pollutants penetration into the water body, decreases the capacity to carry out self-purification of toxic loads. The water pollutant load-carrying capacity is then calculated through various methods, one of which is the use of a computerized numerical modeling simulation called WASP (Water Quality Analysis Simulation Program). This method was developed by the ES-EPA, in order to process TMDLs (Total Maximum Daily Loads) data on river bodies, as well as examine each part of the water quality, based on spatial and temporal inputs. This study was conducted at the Karang Mumus Sub-watershed flowing through the centre of Samarinda City, with aims to determine the pollutants' carrying capacity, existing load, and toxic waste allocation, via the use of the BOD (Biological Oxygen Demand) technique as a parameter of water quality. The calculation was carried out by segmenting the river into five parts, based on the number of districts it passes through, during pollutant loads inventory. The WASP modeling simulation showed that the total pollutant load-carrying capacity of the whole segments was 5,670 kg/day. It also showed the existing loads of about 3,605 kg/day, with the margin having the ability to receive pollutants at 2,065 kg/day. Moreover, the allocation of pollutant loads varies for each segment, with 2, 3, and 4 observed to reduce the pollutant by 390, 220, and 10 kg/day, respectively. However, segments 1 and 5 were still allowed to receive pollutant loads up to 1,740 and 945 kg/day, respectively.